Comparison of Maxillary Molar Distalization with an Implant-Supported Distal Jet and a Traditional Tooth-Supported Distal Jet Appliance. (11th June 2014) - Cozzani, Mauro; Pasini, Marco; Zallio, Francesco; Ritucci, Robert; Mutinelli, Sabrina; Mazzotta, Laura; Giuca, Maria Rita; Piras, Vincenzo
Abstract : Aim . To investigate and compare the efficiency of two appliances for molar distalization: the bone-anchored distal screw (DS) and the traditional tooth-supported distal jet (DJ) for molar distalization and anchorage loss. Methods. Tests (18 subjects) were treated with a DS and controls (18 subjects) were treated with a DJ. Lateral cephalograms were obtained before and at the end of molar distalization and were analysed. Shapiro Wilk test, unpaired t -test, and Wilcoxon rank-sum test were applied according to values distribution. The α level was fixed at 0.05. Results . Maxillary first molars were successfully distalized into a Class I relationship in all patients. The mean molar distalization and treatment time were similar in both groups. The DS group exhibited a spontaneous distalization (2.1 ± 0.9 mm) of the first premolar with control of anchorage loss, distal tipping, extrusion, and skeletal changes. Conclusions . The DS is an adequate compliance-free distalizing appliance that can be used safely for the correction of Class II malocclusions. In comparison to the traditional DJ, the DS enables not only a good rate of molar distalization, but also a spontaneous distalization of the first premolars.